Pattern of Temperature Structures in Himalayan Subduction Zone: A Review - Hossain, Ismail; Islam, Md Rezaul (Journal of Life and Earth Science, 2014)
The present study deals with the temperature structures (e.g., mantle wedge and slab) in Himalayan subduction zone. The estimated maximum temperature in the mantle wedge, Tr is 1420°C, whereas temperature at the top of the slab, Ts ranges from 1081.31119.5°C. The average value of the temperature and standard deviation at the top of the slab is 1103±10.7°C. The study shows that the temperature of the mantle wedge is more or less stable and the slab temperature of the entire Himalayan belt is slightly varied. The mantle wedge temperature of the Himalayan subduction zone is correlated with Kamchatka subduction zone (1450ºC) and Tohoku subduction zone (1400°C) in Northeast Japan. From overall observation, the Himalayan subduction zone is characterized with high compression and high seismic activity of the entire tectonic boundary along both the eastern and western sections. In these contexts, there might have a great possibility for large earthquakes to creep up in this region. The results of the research may contribute to explain geometry, rheology, heat transport and petrological processes of Himalayan subduction zone. Generally a temperature dependent process in the mantle wedge is responsible for the focusing of volcanic activity at the sharp fronts to the arcs. DOI: http://dx.doi.org/10.3329/jles.v7i0.20116 J. Life Earth Sci., Vol. 7: 15-20, 2012